Local Wisdom and Qur’anic Moderation: Analysis Pappaseng Ogi in Tafsir Bugis Al-Munir - Abd. Haris; Nurfaika (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2025)
This study examines the values of moderation in Pappaseng Ogi (Bugis traditional wisdom) and their correlation with Quranic teachings in the context of fostering harmonious societal living. Employing content analysis methodology, this research aims to explore the role of Pappaseng Ogi as a medium for disseminating humanistic values and civilizational principles. The findings reveal a significant congruence between the moderation values inherent in Pappaseng Ogi and the principles of moderation espoused in the Quran. The study successfully identifies five key values of Pappaseng Ogi: assiwollong-pollongeng, assisompungeng, assipakalebbireng, assiamase-maseng, and assifakario-riongeng, which potentially constitute a culture-based model of moderation. These findings demonstrate how indigenous wisdom can be integrated with universal teachings to cultivate moderation and social harmony. This research contributes to the development of a culturally-rooted understanding of religious moderation, with potential practical applications in building social cohesion, promoting tolerance, and managing conflicts. While primarily focused on Bugis society, the findings suggest potential adaptability to other cultural contexts, thus offering broader implications for the study of religious moderation in diverse societies